ESTIMATION OF THE STATE OF ZONES ESOPHAGOGASTRODUODENAL IN DIFFERENT FORMS OF ACUTE PANCREATITIS. (Ta'limning zamonaviy transformatsiyasi, 2024)
It was found that in acute destructive pancreatitis occur microcirculation system changes, both in the breast tissue, and other organs and systems. [1-2]. One of the most sensitive to hypoxia arising structures is the mucous membrane of the digestive tract. [3]. It is known that erosive lesions of the mucous membrane of the esophagus, stomach, duodenum often occurs in acute pancreatitis, but it is unclear whether there is a relationship between the degree of change in this area and the severity of acute pancreatitis. [4-7].